Direitos humanos e cosmopolitismo em Habermas: uma abordagem a partir da razão comunicativa em relação ao direito - Klein, Stefian Metzen (2016)
In an increasingly interdependent society, the perspective of cosmopolitanism presents itself as a possibility of political reorganization of the international environment facing to the challenges posed by the continuous interconnection of national communities. To this end, law is a means of coordination between parties so that such an intention of a cosmopolitan community can be achieved. Considering this post-national scene, human rights seem to be the cornerstone in the construction of a cosmopolitan law that would have the guarantee of human dignity at its foundation. Such is the context in which this work is conceived when it revisits Jürgen Habermas‟s thinking about the legitimacy of law to try to find the basis for a regulatory agreement on human rights and from a cosmopolitan viewpoint. Thus, it begins with a brief overview of the author‟s theory of communicative action and its relation to law. Next, it demonstrates Habermas‟ legal and philosophical theory amid the procedural aspect of law and its respective legitimacy. Finally, it draws on the most recent writings of the philosopher, which affect the current reality, to examine the possibilities of a cosmopolitan identity among world‟s citizens. Additionally, it seeks to analyze an organizational outline proposed by the author to make the transition from an international to a cosmopolitan community, in which moral is perceived as the bridging principle in this context of transnational regulation.